A Case of Bilateral Adnexal Cyst Cured by Natrum Muriaticum (Advancements in Homeopathic Research, 2022)
Mrs S.S. aged about 27 years nulliparous patient a post chemotherapy, post operated case of Ca breast reported on 03/03/2019 for the treatment of Bilateral adnexal cysts with recurrent pain in lower abdomen since September 2018. Menses were regular, scanty lasting 3-4 days. LMP 04/02/2019. Her registration number is S-13392 (B/L O.C.-90) Initial Ultrasonography (27/02/2019):Well defined Bilateral adnexal cysts measuring 71 x 62 mm on right showing another cystic structure within it and 45 x 36 mm on left. Patient was very depressed due to repeated saddening events that took place in her life. Father died in 2010 and mother in 2016. Got married in January 2017 and became very disappointed and depressed due to rude and dominating nature of mother-in-law. she developed a hard lump in right breast which was diagnosed as malignant growth in April 2017.
Keywords: Initial Ultrasonography; Bilateral adnexal cysts; chemotherapy